FACTORS RELATED TO HYPEREMESIS GRAVIDARUM IN FIRST TRIMESTER PREGNANT WOMEN AT THE SOUDAH INDEPENDENT MIDWIFE PRACTICE (PMB), MUARA DUA DISTRICT, LHOKSEUMAWE CITY IN 2023 - Fika Maulid; Nelva Riza; Sri Rezeki (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Hyperemesis gravidarum is vomiting that occurs until 20 weeks gestation, vomiting so intense that everything eaten and drunk is regurgitated that it affects the general condition and daily work, weight loss, dehydration. The incidence of hyperemesis gravidarum in Indonesia is from 1% to 3% of all pregnancies. The purpose of this study was to determine the factors associated with hyperemesis gravidarum in 1st trimester pregnant women at PMB Soudah, Muara Dua District, Lhokseumawe City in 2023. This type of research is an Analytical Survey with Cross Sectional Design, all first trimester pregnant women who experience hyperemesis gravidarum found at PMB Soudah Muara Dua District in March - May 20 23, namely as many as 30 respondents. Data retrieval techniques use primary data. The analysis used in this study was univariate and bivariate with chi square statistical test. The results of the study based on the chi square test showed that the variables of age p-value 0.023 (<0.05), p-value parity 0.018 (><0.05), husband support p-value 0.026 (><0.05), work p-value 0.007 (><0.05) which means there is a significant relationship between age, parity, husband support, and work with hyperemesis gravidarum in first trimester pregnant women. Conclusion from This study is a relationship between age, parity, husband support, and work with hyperemesis gravidarum in first trimester pregnant women at PMB Soudah, Muara Dua District, Lhokseumawe City in 2023. It is recommended that Haamil mothers make regular ANC visits and carry out information obtained from><0.05), p-value parity 0.018 (<0.05), husband support p-value 0.026 (<0.05), work p-value 0.007 (<0.05) which means there is a significant relationship between age, parity, husband support, and work with hyperemesis gravidarum in first trimester pregnant women. Conclusion from This study is a relationship between age, parity, husband support, and work with hyperemesis gravidarum in first trimester pregnant women at PMB Soudah, Muara Dua District, Lhokseumawe City in 2023. It is recommended that Haamil mothers make regular ANC visits and carry out information obtained from health workers to prevent and overcome the incidence of hyperemsis gravidarum.